Analysis of performance, combustion and emission parameters in di diesel engine by using mahua methyl ester along with nano metal additives titanium dioxide. (2021) - Udaya Kumar, M.; Sivaganesan, S.; Dhanasekaran, C.; Parthiban, A.
Abstract: Current scenario is look at Non conventional alternative fuel source to decrease its dependence on the foreign import of various oils. Amongst all alternative fuel offered Mahua oil, in which is changed to bio - diesel by means of transesterification process. The adding up of nano-metal additive to biodiesel during a variety of form considerably improves the properties and it contributes to improved behaviour of diesel engine by reduced emission. The experimental work is done to found the behavior, combustion and emission characteristic in the diesel-engine by means of Biodiesel fuels and Nano-metal Additives Titanium Dioxide. The Bio diesel is prepared by transesterification processes, then powder metal oxide is converted in to nano form by means of ball milling, CTAB (Cetyl Trimethyl Ammonium Bromide) is taken as cationic agent, then known quantity of TiO2 and CTAB Nano metal additives is mixed with the base fluid Mahua oil Methyl Ester (MOME) which is the biodiesel by Ultrasonication process. The blend which is obtained is tested by single cylinder four stroke diesel engines and can be noted that the adding of nano metal additive in the bio diesel improves the behavior, combustion and the emission characteristics of diesel-engine.